Assessing the Impact of Migration on Food and Nutrition Security - Zezza, Alberto (2012)
Migration has become a key component in the livelihood strategies of an increasing number of households across the developing world and remittances have expanded dramatically in the last decade. This has come at a time when an increased emphasis has been placed on reducing malnutrition to achieve Millennium Development Goal (MDG) targets. While this is the case, there has been little attention on the interface between migration and nutrition even though migration can influence nutrition through a number of channels. The objective of this special issue is to present state-of-the-art analyses of the link between migration and nutrition in developing countries. In this paper, an overview of the conceptual and empirical issues in identifying the link between migration and nutrition are considered. Further, the results from seven country case studies are synthesized and policy implications are drawn.